A cloudy epiphany / Sharifah Syakila Syed Shaharuddin - Syed Shaharuddin, Sharifah Syakila (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.